Medico-legal issues in infectious diseases guide for physicians - Fong, I. W. (Ignatius W.) (Emerging infectious diseases of the 21st century., 2011)
Despite the fact that most physicians will encounter medical litigation at some point in their careers, they have few resources for navigating through legal issues within the body of medical literature. With this in mind, this volume provides guidance to physicians and researchers.  As the latest in the Emerging Infectious Diseases of the 21st Century series, it gives case scenarios in the format of problem-solving challenges faced by physicians in various practices and subspecialties. It covers topics including issues in the surgical and neurosurgical disciplines, obstetrics and gynecological infections, skin/soft tissue conditions, fevers, and complications related to HIV. It also gives information medical liability laws around the world. Rather than encourage defensive medical practice, this book provides information on administering better care and being honest and fair with patients when addressing inevitable mistakes. It is a must for all practicing physicians.